Drug affinity-responsive target stability unveils filamins as biological targets for artemetin, an anti-cancer flavonoid - Ferraro, Giusy; Belvedere, Raffaella; Petrella, Antonello; Tosco, Alessandra; Stork, Björn; Salamone, Stefano; Minassi, Alberto; Pollastro, Federica; Morretta, Elva; Monti, Maria Chiara (Frontiers in Molecular Biosciences, 2022)
Artemetin is a valuable 5-hydroxy-3,6,7,3′,4′-pentamethoxyflavone present in many different medicinal plants with very good oral bioavailability and drug-likeness values, owing to numerous bioactivities, such as anti-inflammatory and anti-cancer ones. Here, a multi-disciplinary plan has been settled and applied for identifying the artemetin target(s) to inspect its mechanism of action, based on drug affinity-responsive target stability and targeted limited proteolysis. Both approaches point to the disclosure of filamins A and B as direct artemetin targets in HeLa cell lysates, also giving detailed insights into the ligand/protein-binding sites. Interestingly, also 8-prenyl-artemetin, which is an artemetin more permeable semisynthetic analog, directly interacts with filamins A and B. Both compounds alter filamin conformation in living HeLa cells with an effect on cytoskeleton disassembly and on the disorganization of the F-actin filaments. Both the natural compound and its derivative are able to block cell migration, expectantly acting on tumor metastasis occurrence and development.